Communication of different assurance levels. - Huang, Xuefen. (2008)
Our study investigates whether contrast for work performed in assurance reports would help low assurance knowledge consumers to better distinguish between high and moderate assurance levels provided in an assurance report. The findings suggest that contrast did help them to differentiate but have no significant effect on their purchase intentions.